From static pathology to dynamic immunity: immunological plasticity and histopathological remodeling in atopic dermatitis and psoriasis - Shen, Wei; Yao, Yi; Ma, Ying-Ming; Xie, Xiao-Lei; Tang, Shun-Li; Wu, Yuan; Zhong, Hua-Jie; Li, Yu-Mei; Sun, Hui (Frontiers in Immunology, 2026)
Atopic dermatitis (AD) and psoriasis are the two canonical chronic inflammatory skin disorders, classically differentiated by their distinct histopathological features and immune polarization—Th2-dominant in AD versus IL-23/Th17-dominant in psoriasis. However, this conventional dichotomy is increasingly contested by clinical observations, such as the mixed immunophenotypes seen in Asian AD and overlap syndromes, which complicate clear-cut classification. Growing evidence highlights substantial immunological plasticity and pathological overlap, suggesting that these diseases may represent segments of a continuous spectrum rather than discrete entities. In this Mini Review, we integrate classical morphological observations with recent advances in molecular immunology to explore the mechanisms underlying these tissue responses. We examine how immune cell plasticity—particularly of tissue-resident memory T cells—and their crosstalk with the structural microenvironment contribute to disease heterogeneity and therapy-induced phenotypic shifts. We propose that a shift from static histologic evaluation toward dynamic immunopathological profiling is crucial for narrowing the gap between conventional diagnosis and the emerging paradigm of precision medicine.